Efficient synthesis of varenicline - Pasikanti, Srinivas; Reddy, D. Srinivasa; Venkatesham, B.; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2010)
Synthesis of varenicline the antismoking drug has been achieved in six steps with 10% overall yield. A Diels-Alder reaction, oxidative cleavage of an olefin and reductive amination remain as key steps in the synthesis (C) 2009 Elsevier Ltd. All rights reserved.

Novel pyrazole-3-carboxamide derivatives as cannabinoid-1 (CB1) antagonists: journey from non-polar to polar amides - Sasmal, Pradip K.; Reddy, D. Srinivasa; Talwar, Rashmi; Venkatesham, B.; Balasubrahmanyam, D.; Kannan, M.; Srinivas, P.; Kumar, K. Shiva; Devi, B. Neelima; Jadhav, Vikram P.; Khan, Sanjoy K.; Mohan, Priya; et al. (Bioorganic & Medicinal Chemistry Letters, 2011)
The synthesis and biological evaluation of novel pyrazole-3-carboxamide derivatives as CB1 antagonists are described. As a part of eastern amide SAR, various chemically diverse motifs were introduced. In general, a range of modifications were well tolerated. Several molecules with high polar surface area were also indentified as potent CB1 receptor antagonists. The in vivo proof of principle for weight loss is exemplified with a lead compound from this series. (C) 2010 Elsevier Ltd. All rights reserved.